A case of Peritonitis with pneumoperitoneum secondary to a spontaneous rupture of splenic abscess (Bangladesh Journal of Medical Science, 2022)
Sponteous rupture of a splenic abscess is rare and little described in the literature. It can cause peritonitis with pneumoperitoneum. Our case illustrates this exceptional complication in a 77 year-old diabetic patient who consulted for abdominal pain with asthenia. The abdominal computed tomography showed an acute peritonitis caused by with splenic abscess. Aeoporty was also observed. He was operated but died postoperatively for severe sepsis. Our case is rare and interesting. Indeed, a splenic abscess can be the cause of peritonitis, pneumoperitoneum and aeorportie.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 455-457